2010
DOI: 10.1200/jco.2010.28.18_suppl.lba4518
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial comparing adjuvant paclitaxel/gemcitabine/cisplatin (PGC) to observation in patients with resected invasive bladder cancer: Results of the Spanish Oncology Genitourinary Group (SOGUG) 99/01 study.

Abstract: LBA4518 Background: Approximately half of patients with resected invasive bladder cancer will die within the first three years after surgery due to disease relapse, most of the recurrences being systemic. We have studied in a randomized phase III trial the role of 4 courses of the PGC triplet as compared to observation in this clinical setting. Methods: Eligibility criteria included: (1) resected high-risk muscle invasive bladder carcinoma (pT3-4 and/or pN+), (2) ECOG PS 0-1, (3) adequate renal function (CrC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 0 publications
0
70
0
8
Order By: Relevance
“…17 The same guidelines either do not support adjuvant chemotherapy (ACT), or provide only weak support, due to a lack of information from adequately powered RCTs. Recently, however, results of 3 contemporary randomized trials, [18][19][20] an updated meta-analysis, 21 and 2 large observational studies 22,23 have all consistently demonstrated that ACT also provides benefit to patients.…”
mentioning
confidence: 99%
“…17 The same guidelines either do not support adjuvant chemotherapy (ACT), or provide only weak support, due to a lack of information from adequately powered RCTs. Recently, however, results of 3 contemporary randomized trials, [18][19][20] an updated meta-analysis, 21 and 2 large observational studies 22,23 have all consistently demonstrated that ACT also provides benefit to patients.…”
mentioning
confidence: 99%
“…Si les lignes directrices n'approuvent pas -ou peu -la chimiothérapie adjuvante, c'est à cause du manque d'information provenant d'essais comparatifs à répartition aléatoire ayant une puissance statistique suffisante. Pourtant, les résultats de trois essais contemporains à répartition aléatoire [18][19][20] , de la mise à jour d'une méta-analyse 21 et de deux études observationnelles à grande échelle 22,23 ont démontré récemment que la chimiothérapie adjuvante n'est pas dénuée d'avantages pour les patients.…”
Section: L'auc a Pour Mandat De Promouvoir Les Plus Hautes Normes Danunclassified
“…Individually, some of the older studies included in the analysis had shown improvements in DFS favoring AC without OS data [Skinner et al 1990;Stockle et al 1995;Freiha et al 1996]. More contemporary randomized trials included in the analysis looked at AC with either gemcitabine plus cisplatin versus observation or gemcitabine plus cisplatin and paclitaxel versus observation and had conflicting results, with only the three-drug regimen showing an improvement in outcomes including OS [Paz-Ares et al 2010;Cognetti et al 2012]. With less than 200 patients in each of these contemporary studies, the ability to draw conclusions based on the findings was limited.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%